2020
DOI: 10.1002/adtp.202000115
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Soluble Epoxide Hydrolase with TPPU Alleviates Irradiation‐Induced Hyposalivation in Mice via Preventing Apoptosis and Microcirculation Disturbance

Abstract: IR irradiation-induced dysfunction of the salivary gland and hyposalivation are one of the main complications of radiotherapy treatment for malignant head and neck tumors, and its mechanisms are not fully understood. IR-induced microcirculation disturbance and apoptosis is one of the most important mechanisms. Most recent studies have focused on the regenerative effects of epoxyeicosatrienoic acids (EETs) through the process of increased angiogenesis. This study suggests that increasing endogenous EETs by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 48 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…EETs protect the heart and liver by autophagy regulation 45 , 46 . Our previous study has shown that TPPU can significantly increase angiogenesis, and reduce acinar cell apoptosis and histological damage in ir-injured mice 47 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…EETs protect the heart and liver by autophagy regulation 45 , 46 . Our previous study has shown that TPPU can significantly increase angiogenesis, and reduce acinar cell apoptosis and histological damage in ir-injured mice 47 .…”
Section: Discussionmentioning
confidence: 91%
“…TPPU (Sigma‑Aldrich, Merck KGaA, Darmstadt, Germany) was dissolved in dimethyl sulfoxide (DMSO, Coolaber, Beijing, China) as a stock solution (10 mg/ml), and further diluted to 10 μM TPPU for cell treatment in vitro or 20 μM TPPU for local injection in vivo 26 , 47 . Cells were treated with or without an autophagy inhibitor 3-methyladenine (3-MA, 10 mM; Solarbio, Beijing, China), an autophagy inducer Rapamycin (Rapa, 5 µM; Solarbio, Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
“…3E and 3F ). EMT plays a key role in the process of invasion and metastasis of epithelial tumor cells ( Zhang et al, 2020 ). These results suggested that CCL25 could cause SACC-LM cells to lose polarity and connections with each other and further enhance the degradation of ECM, thus promoting the migration and invasion of SACC cells.…”
Section: Resultsmentioning
confidence: 99%
“…The Colorimetric TUNEL Apoptosis Assay Kit (Vazyme Biotech, Nanjing, China) was used to detect the apoptosis ability of mouse xenograft tumors. According to the manufacturer’s instructions and our previous procedure ( Zhang et al, 2020 ), the tissues were fixed in 4% paraformaldehyde and embedded in paraffin. Next, the tissues were cut into 4 µm sections and then subjected to conventional deparaffinization and hydration.…”
Section: Methodsmentioning
confidence: 99%
“…no. A112-01; Vazyme Biotech, Co., Ltd.) and a previous study by the authors (27). Briefly, the sections were incubated with the Equilibration Buffer for 30 min at room temperature and then marked with the labeling mix buffer for 1 h at 37˚C.…”
Section: Reverse Transcription-quantitative Polymerase Chain Reaction...mentioning
confidence: 99%